1997
DOI: 10.1097/00006454-199712000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A glycoprotein pneumococcal conjugate vaccine primes for antibody responses to a pneumococcal polysaccharide vaccine in Gambian children

Abstract: Vaccination of young infants with two or three doses of a pneumococcal conjugate vaccine primes the immune system to respond strongly and rapidly on subsequent exposure to pneumococcal polysaccharide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 14 publications
2
34
0
1
Order By: Relevance
“…Protective immunity against both invasive disease [16,17] and otitis media [18] has been demonstrated after vaccination of infants with pneumococcal conjugate vaccines. In addition, pneumococcal conjugate vaccines induce PS-specific memory B cells [19][20][21], similar to what has been observed after immunization with protein antigens.…”
Section: Introductionsupporting
confidence: 56%
“…Protective immunity against both invasive disease [16,17] and otitis media [18] has been demonstrated after vaccination of infants with pneumococcal conjugate vaccines. In addition, pneumococcal conjugate vaccines induce PS-specific memory B cells [19][20][21], similar to what has been observed after immunization with protein antigens.…”
Section: Introductionsupporting
confidence: 56%
“…Previous authors have commented that the most common pneumococcal serotypes that cause infections in children are the poorest immunogens in this age group (10,20). The poor immunogenicity of serotype 6B polysaccharide for example has been observed in previous studies (27,44) and might make conditions more favorable for persistent carriage of pneumococci bearing the 6B capsule. In carriage studies, including the data presented here, serotype 6B pneumococci are more frequently isolated than many other serotypes (6,24).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, in (1,44). In addition, we and others have shown that PCVvaccination can overcome the impaired immune response to the plain pneumococcal polysaccharide in certain risk groups (22,30,32,39,41,46,55). However, antibody concentrations are not the only correlate of a protective immunity.…”
Section: Discussionmentioning
confidence: 96%
“…As we know from Haemophilus influenzae, conjugate vaccine efficacy is also determined by differences in the kinetics of immune response (17). Demonstration of B-cell memory has largely been based on a rapid and strong antibody response to a dose of plain polysaccharide vaccine after priming with a conjugate vaccine (32,33,54). There are only limited data on the kinetics of immunological memory in high-risk groups.…”
Section: Discussionmentioning
confidence: 99%